Pendidikan Islam Berbasis Multiple Intelligences - Husna, Difa'ul; Salsabila, Unik Hanifah; Ichsan, Yazida (TADRIS: Jurnal Pendidikan Islam, 2020)
Education becomes one of the ways and processes for improving mental attitudes and developing human potential in order to lift the degree of humanity. As an institution that has a strategic role in society, then ideally every learning activity in the school should be directed to develop potential through activities that effectively also refer to the compound intelligence of its students. This research includes qualitative research that prioritizes excavation, explanation and delivery of the express and implied meaning of the data collected. This research was conducted to find out how Islamic education based on multiple intelligences. Data collection is done by looking at reading materials from previous theories, concepts and research results to be reduced, grouped and identified valid and relevant data. One of the efforts in implementing Islamic Religious Education learning that stimulates multiple intelligences is to creatively prepare lesson plan based on the results of the study style of students. In addition, in the process it is necessary to use active learning strategies that involve different types of student intelligence as well as provide experience in factual problem solving. Learning should also be supported by evaluation in the form of authentic assessments that are useful to observe the development as well as the learning results of students periodically and thoroughly.